Charge distribution guided by grain crystallographic orientations in polycrystalline battery materials - Xu, Zhengrui; Jiang, Zhisen; Kuai, Chunguang; Xu, Rong; Qin, Changdong; Zhang, Yan; Rahman, Muhammad Mominur; Wei, Chenxi; Nordlund, Dennis; Sun, Cheng-Jun; Xiao, Xianghui; Du, Xi-Wen; et al. (Nature communications, 2020)
Architecting grain crystallographic orientation can modulate charge distribution and chemomechanical properties for enhancing the performance of polycrystalline battery materials. However, probing the interplay between charge distribution, grain crystallographic orientation, and performance remains a daunting challenge. Herein, we elucidate the spatially resolved charge distribution in lithium layered oxides with different grain crystallographic arrangements and establish a model to quantify their charge distributions. While the holistic “surface-to-bulk” charge distribution prevails in polycrystalline particles, the crystallographic orientation-guided redox reaction governs the charge distribution in the local charged nanodomains. Compared to the randomly oriented grains, the radially aligned grains exhibit a lower cell polarization and higher capacity retention upon battery cycling. The radially aligned grains create less tortuous lithium ion pathways, thus improving the charge homogeneity as statistically quantified from over 20 million nanodomains in polycrystalline particles. This study provides an improved understanding of the charge distribution and chemomechanical properties of polycrystalline battery materials. The authors here report on the influence of grain orientation on the charge distribution in polycrystalline materials for batteries. The quantitative characterization provides mechanistic insight into the way the grain orientation can be engineered to mitigate the charge heterogeneity.